Socio-Cultural Significances of Teej Festival in Nepalese Society (Voice of Teacher, 2025)
Festival Teej fosters as a vibrant embodiment of religious devotion, cultural meaning and social unity among the Brahmin, Chhetri, and Thakuri community’s women in Nepali Hindu society. It is deeply connected in Hindu myth and ritual with the symbolizing the ideal of marital bond, spiritual purity and the strength of feminine devotion. This study aims to explore importance of Teej festival among the Brahmin, Chhetri, and Thakuri community’s women of Nepal. This study has used a qualitative methods approach to investigate the socio-cultural importance of Teej in Nepali society. The qualitative information was collected through the emic approach. This study tries to explore the exact socio-culture scenario of Teej in Nepali society, and discussed different issues like, past records, traditional information for the proper explanation of the glory festival Teej in Nepali society. The festival Teej has the socio-cultural and religious meaning among the Brahmin, Chhetri, and Thakuri community’s women of Nepali Hindu are observed. It refers to dedication to Goddess Parvati and her union with Lord Shiva. The festive symbolizes marital devotion, spiritual purity, and the wellbeing of the husband and family. Unmarried girls also observe the festive and fast believing with getting an ideal husband. On the month of Bhadra (August–September), they use three days for the ritual and religious purposes like “Dar Khane" feasts, fasting (Nirjala Brata), and purification procession on Rishi Panchami. It is mythological rooted traditions under this festive Teej, women have a space for expressing womanhood and sisterhood through song, dance, and traditional attire. The festival has undergone visible transformations because of globalization, commercialization, and political involvement, even it continues to develop as a significant platform for women to express about the personal and collective experiences. Any way it helps to concerns about the dilution of traditional values, the changes have also help to open up the space for empowerment, awareness, and visibility in society. So, the festive Teej has a meaningful and significant role to intersect the tradition and modernity with upholding spiritual belief while reflecting the socio-cultural realisms in present Nepal.